2017
DOI: 10.1093/pasj/psx063
|View full text |Cite
|
Sign up to set email alerts
|

Hyper Suprime-Cam: System design and verification of image quality

Abstract: The Hyper Suprime-Cam (HSC) is an 870 megapixel prime focus optical imaging camera for the 8.2 m Subaru telescope. The wide-field corrector delivers sharp images of 0${^{\prime\prime}_{.}}$2 (FWHM) in the HSC-i band over the entire 1${^{\circ}_{.}}$5 diameter field of view. The collimation of the camera with respect to the optical axis of the primary mirror is done with hexapod actuators, the mechanical accuracy of which is a few microns. Analysis of the remaining wavefront error in off-focus stellar images re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
206
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(209 citation statements)
references
References 38 publications
0
206
0
Order By: Relevance
“…The results presented in the previous section are predictions for the established Subaru HSC Deep field, which has a field of view of ∼ 27 deg 2 and a depth of r ∼ 27 (Miyazaki et al 2018;Ouchi et al 2018). In Figure 9 we demonstrate the effect of expanding the LAE survey in either area or depth, in combination with an SKA 21-cm survey at z = 6.6.…”
Section: Future Survey Sensitivitiesmentioning
confidence: 79%
See 2 more Smart Citations
“…The results presented in the previous section are predictions for the established Subaru HSC Deep field, which has a field of view of ∼ 27 deg 2 and a depth of r ∼ 27 (Miyazaki et al 2018;Ouchi et al 2018). In Figure 9 we demonstrate the effect of expanding the LAE survey in either area or depth, in combination with an SKA 21-cm survey at z = 6.6.…”
Section: Future Survey Sensitivitiesmentioning
confidence: 79%
“…(2015); Chang et al (2015). e We assume a narrowband (∆z = 0.1) survey geometry, based on Miyazaki et al (2018); Takada et al (2014). † Observing at 150 MHz.…”
Section: Reionization Historiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To study AGN variability on decade timescales, we identified AGN from the SDSS (York et al 2000) DR7 Quasar catalog (Schneider et al 2010) that were also observed later by the Hyper Suprime-Cam (HSC; Miyazaki et al 2018) Subaru Strategic imaging survey. The SDSS survey used a dedicated 2.5 m (Gunn et al 2006) telescope at Apache Point Observatory to obtain images in five optical bands (ugriz) over a large patch (∼10000 deg 2 ) of the northern sky.…”
Section: Datamentioning
confidence: 99%
“…In our companion papers (Chiu et al 2018;Sereno et al 2018), we explicitly account for the effects of triaxiality in forwardmodeling our multiprobe data sets, simultaneously constraining the cluster mass, concentration, triaxial shape, and orientation from Bayesian inference. Extending this analysis with large, well-controlled samples of clusters from ongoing and planned surveys, such as the XXL survey Pierre et al 2016), the Subaru Hyper Suprime-Cam survey (Mandelbaum et al 2018;Miyazaki et al 2018aMiyazaki et al , 2018bOguri et al 2018), the Dark Energy Survey, and the WFIRST and Euclid missions, will be a significant step forward in understanding the tidal and evolutionary effects of surrounding LSS on the intracluster mass distribution.…”
mentioning
confidence: 99%